Neurofilament heavy phosphorylated epitopes as biomarkers in ageing and neurodegenerative disease - De Paoli, Laura F.; Kirkcaldie, Matthew T. K.; King, Anna E.; Collins, Jessica M. (Journal of neurochemistry, 2025)
From the day we are born, the nervous system is subject to insult, disease and degeneration. Aberrant phosphorylation states in neurofilaments, the major intermediate filaments of the neuronal cytoskeleton, accompany and mediate many pathological processes in degenerative disease. Neuronal damage, degeneration and death can release these internal components to the extracellular space and eventually the cerebrospinal fluid and blood. Sophisticated assay techniques are increasingly able to detect their presence and phosphorylation states at very low levels, increasing their utility as biomarkers and providing insights and differential diagnosis for the earliest stages of disease. Although a variety of studies focus on single or small clusters of neurofilament phosphorylated epitopes, this review offers a wider perspective of the phosphorylation landscape of the neurofilament heavy subunit, a major intermediate filament component in both ageing and disease. Aberrant phosphorylation states in neurofilaments, intermediate filaments of the neuronal cytoskeleton, accompany and mediate pathological processes in neurodegenerative diseases. Neuronal degeneration and death can release neurofilaments into the extracellular space and eventually the cerebrospinal fluid and blood. Sophisticated assay techniques are increasingly able to detect their presence and phosphorylation states at very low levels, increasing their utility as diagnostic and prognostic biomarkers in the earliest stages of disease. Although a variety of studies focus on single or small clusters of neurofilament phosphorylated epitopes, this review offers a wider perspective of the phosphorylation landscape of the neurofilament heavy subunit, a major neurofilament component in both ageing and disease. Created in BioRender. De Paoli, L. (2024) https://BioRender.com/b94a335.